GLOBALIZATION AND ITS IMPACT ON INTERNATIONAL ECONOMIC RELATIONS - Zebiniso Igamberdieva (Web of Journals Publishing, 2024)
The article discusses characteristics of globalization and what role does globalization play in international economic relations? Statistical data shows that Globalization has changed the picture of World Economy as a result of the growing scale of cross-border trade of commodities and services, exchange of currency, movement of people and flow of information.
Keywords: Globalization; interdependence of world on different levels of : economics, politics and socials; global competition; variety of choices for consumers.